Biomechanical report for the IAAF World Indoor Championships 2018 high jump men - Nicholson, G.; Bennett, T.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The men`s high jump final took place on the night of Thursday 1st March in the centre of the infield, back to back with the women`s final, which took place simultaneously. Despite having cleared a world-leading 2.38 m in Tehran in early February, the reigning IAAF outdoor world champion Mutaz Essa Barshim from Qatar came into the event with some technical challenges. Meanwhile, Danil Lysenko competing as an authorised neutral athlete had registered lifetime bests on three occasions in the winter period leaping to 2.38 m in Hustopeèe in late January. Although none of the Birmingham finalists surpassed their season`s best, the high jump produced the first surprise of the championships. In a reversal from the 2017 contest in London, it was the world silver medallist Lysenko who leapt to victory above Barshim taking his first major international title. Both Lysenko and Barshim enjoyed first time clearances at 2.20 m, 2.25 m, 2.29 m and 2.33 m. Although Barshim was close to clearing 2.36 m in his second attempt, Lysenko produced a superb final leap to clear 2.36 m, just one centimetre short of his lifetime best. Despite coming into the competition ranked 13th in the 2018 world list, it was German`s Mateusz Przybylko who claimed the bronze medal with a second-time clearance at 2.29 m. Przybylko fended off the close challenge of the 2012 Olympic medallist Erik Kynard who needed all three attempts to clear 2.29 m. The European indoor champion Sylwester Bednarek claimed fifth place with a first-time clearance of 2.25 m leaving Wang Yu of China, former world champion Donald Thomas (Bahamas) and the European junior champion Maksim Nedasekau (Belarus) in a tie for sixth place having all recorded first time clearances at 2.20 m.